The state of knowledge in social self-efficacy among international students: A systematic literature review - Nguyen, Tri Dang; McGregor, Marie (Journal of International Students, 2025)
To examine the existing body of empirical research on social self-efficacy in international students, a systematic review of the peer-reviewed literature was conducted, with a focus on articles published between 2013 and 2024. Four inclusion and exclusion criteria guided the search process across the Scopus, ProQuest, PsycINFO, and ERIC databases. A total of ten studies met the inclusion criteria, with thematic synthesis revealing three themes: psychological adjustment, social interaction, and university support. We reflect on these themes concerning supporting the social self-efficacy of international students. Our findings underscore the need for future research in this area while initiating a conversation on how tertiary institutions can effectively support international students.